IMPLEMENTASI APLIKASI QUIZIZZ PADA EVALUASI PEMBELAJARAN IPS DI KELAS VIII C SMP NEGERI 2 PANGENAN KABUPATEN CIREBON - Nurizzati, Yeti; Jamaro, Eriko; Nuryana, Nuryana (Universitas Negeri Makassar, 2024)
This The purpose of this research is to find out how to plan learning evaluations, to know how to carry out learning evaluation, and to know what are the driving factors and obstacles to learning evaluation using the Quizizz application in social studies subjects in class VIII C at SMP Negeri 2 Pangenan. The type of research used in this research is descriptive quantitative method. The sample in this study was 38 students in class VIII C of SMP Negeri 2 Pangenan. Data collection instruments in this research used questionnaires, documentation and observation. data analysis technique uses data percentage analysis. Based on the results of learning evaluation planning research using the Quizizz application by making a Learning Implementation Plan (RPP) in social studies learning at SMP Negeri 2 Pangenan obtaining a result of 91.25%, meaning that it is included in the 'Very Good' category. the research results from the implementation of learning evaluation using the Quizizz application in social studies learning at SMP Negeri 2 Pangenan obtained a result of 77.4%, meaning it was declared to be in the